Enhance Operational Efficiency of Manufacturing Process Using Six Sigma in Small Scale Manufacturing Industry: DMAIC Approach - Kumar, Narender; Kumar, Raj (SOTVI, 2024)
An effective framework for driving process enhancement and boosting operational efficiency in the manufacturing sector has developed as the Six Sigma DMAIC approach. Focusing on its capacity to methodically detect and resolve process inefficiencies, minimise defects, and optimise performance, this article investigates the implementation for Six Sigma DMAIC concepts in manufacturing. According to the research, it's crucial to set precise objectives for each project and measure success based on those goals in order to implement focused improvement efforts at the manufacturing plant The importance of data-driven decision-making, stakeholder participation, and a culture of continuous improvement in generating sustainable outcomes is highlighted in the article via a thorough analysis of the four DMAIC phases—Define, Measure, Analyse, Improve, and Control. In order to successfully apply DMAIC, the results highlight the need of leadership buy-in, employee agency, and cross-functional cooperation. In today's fast-paced manufacturing industry, staying ahead of the competition is crucial. To achieve continuous improvement, customer satisfaction, & long-term success, manufacturing organisations must embrace the Six Sigma DMAIC concepts.